Editor's introduction - Franklin G. Mixon (Economies, 2019)
Technology and innovations have fueled the evolution of the fourth industrial revolution (Industry 4.0). Industry 4.0 spurs growth and development through its efficiency capacity, as documented in the literature. The growth of the construction industry is a subset of the universal set of the value of gross domestic product, and thus, industry 4.0 has a spillover effect on the engineering and construction industry. The aim of this paper is to map the state of Industry 4.0 in the construction industry from the point of view of manarial activities, such as investment management, project preparation, and an overall approach to the management of related activities. This study employed scoping review techniques to dissect the status quo for Industry 4.0 and the construction industry. The empirical results from the systematic and scoping review methods for the ten sampled publications revealed that information and communication technology (ICT)-Industry 4.0-has a significant positive impact on the growth of the construction industry. Therefore, construction practitioners should partner more with researchers in the ICT industry to enhance the automation of work processes and managerial activities in the engineering and construction industry.
Keywords: 330